Twenty-four cases of the EEC syndrome: clinical presentation and management. Issue 9 (September 1995) - Buss, P W; Hughes, H E; Clarke, A
Abstract : Twenty-four cases of EEC syndrome were identified as part of a nationwide study. Ectodermal dysplasia, by study definition, was present in all cases and hair and teeth were universally affected. Nail dysplasia was present in 19 subjects (79%) and the skin was affected in 21 (87%). The presence of hypohidrosis was not noted as a predominant feature in the syndrome and its occurrence appeared to depend on the presence of all other features. Distal limb defects from simple syndactyly to tetramelic cleft hand and foot were identified, including preaxial anomalies. Orofacial clefting was identified in 14 cases (58%) and lacrimal duct anomaly in 21 (87%). Significant clinical problems encountered were chiefly cosmetic or ophthalmological, but conductive deafness and genitourinary problems in some cases required surgical intervention. Altered self-image was also noted in some cases. Multidisciplinary management is necessary with the early involvement of the clinical geneticist. Developmentally, the EEC syndrome and related disorders represent disorders of ectodermal/mesodermal interaction. Candidate regions include 7q21.3, the "ectrodactyly" locus; other candidates include developmental genes implicated in the ectodermal/mesodermal interactive process.